Peculiarities of topographic anatomy and crypt compartment of distal colon in Wistar rats - A. D. Kim; O. A. Goldberg; S. A. Lepekhova; E. V. Koval; T. V. Fadeeva; L. R. Shedoeva; E. Y. Chashkova (Acta Biomedica Scientifica, 2016)
We studied distal colon of Wistar rats including descending transverse colon and rectum. Feature of distal colon in the left flexure are short mesenterium growing in size towards rectum, common mesenterium with small intestine attached to it on the right side and ligament forming left flexure and attached to it on the left side. It was found that one of the variants of normal blood supply is the absence of a. mesenterica caudalis. In this case blood supply comes from arterial arch formed by a. rectalis media and a. colica media. Moreover, in the classic variant of blood supply we revealed a variation in the amount of straight branches that go to this segment of colon wall from left colic and superior rectal arteries (from 3 to 5 from each artery). The structural features of rectum is weak expression of rectal ampulla that causes the depletion of fecal masses immediately after passing into rectum. Crypt compartment of colon of Wistar rats consists by 80,6 % of obligatory flora represented with Bacteroides ssp., Lactobacillus spp., Bifidobacterium spp., Enterococcus faecalis, E. coli (lac+), Grampositive rods. Facultative flora is represented with Proteus mirabilis, Peptococcus spp., Candida spp., Staphylococcus epidermidis, Citrobacter freundii and makes 19,4 %.